Improvement of Hot Laboratory Facilities in Nuclear Medicine - Quadir, Kamila Afroj; Khatun, Nurjahan; Hoque, Md Ashraful; Begum, Aleya (Bangladesh Journal of Medical Physics, 2013)
A Hot-Lab is the major source of radiation exposure by medical technicians in a nuclear medicine set up. A table top bench shield is used to reduce this exposure which consists of a lead base and a lead wall in the bottom part while a viewing window is provided in the top part through the use of thick glass or leaded glass. In our laboratory, a home-made shield was used earlier which incorporated a 254mm ordinary glass window in the top and a thick lead wall at the bottom part. Recently a commercial bench shield was procured that uses a lighter lead glass window for better viewing. This lead glass gives an equivalent lead thickness of 2.2 mm. The present work was taken up to study the changes in the radiation exposure to nuclear medicine technicians due to this change in the bench shield. The effective doses received by two technicians were 0.937 mSv and 1.098 mSv respectively when they worked for two months using the old table top bench shield. This dose came down substantially to 0.292 mSv and 0.187 mSv respectively, when they used the new table top bench shield for the same period of time. Side by side, the radiation reaching the outer surfaces of the glass shield and the lead wall were measured due to a radiation source placed at 0mm, 10mm and 20mm from the respective inner surfaces. For the lead shield the dose rates were not much different between the two models, but for the glass window, the commercial one gave much reduced dose rate. Although the dosage was higher in the indigenously made device, the duty schedules of the technicians were rotated so that none received dosage greater than safe limits over a full year. DOI: http://dx.doi.org/10.3329/bjmp.v5i1.14669 Bangladesh Journal of Medical Physics Vol.5 No.1 2012 37-40